Ethnopharmacology and bioactive evidence of medicinal plants for wound healing in Indonesia: A scoping review - Dewa Ayu Swastini, Ronny Martien, Jajah Fachiroh, Agung Endro Nugroho (Journal of Applied Pharmaceutical Science, 2025)
Wounds damage the skin, disrupting its normal structure and function. This review discusses medicinal plants commonly used to treat wounds in Indonesia, including their ethnopharmacology, active compounds, and molecular targets that support their bioactive properties. Data were gathered from electronic databases published between 2000 and 2023, such as Web of Science, PubMed, Google Scholar, Scopus, and ScienceDirect. A descriptive analysis was conducted on 94 articles covering ethnopharmacy, phytochemicals, in vitro and in vivo investigations of the effectiveness of medicinal plants against wound healing. A total of 238 plant species from 60 families have been reported to be used for wound healing in Indonesia. Ursolic acid, curcumin, aloin, emodin, quercetin, kaempferol, luteolin, lantadene, jatrophone, allicin, eugenol, and gingerol are among the chemical components linked to this action that promote wound healing. Herbal medicines can target multiple molecular targets to encourage wound healing, including cytokines interleukin (IL-1, IL-6, IL-10, COX-1, and COX-2), growth factors (tumor necrosis factor-alpha, transforming growth factor-β1, vascular endothelial growth factor), and signaling molecules (reactive oxygen species). Furthermore, we found that herbal medicine targeted mitogenic pathways, such as protein kinase B, phosphoinositide 3-kinase, and smooth muscle actin. Resource monitoring, phytochemical and pharmacological research, and evidence-based drug development can support traditional medicine and facilitate drug discovery, potentially leading to the development of novel drugs for wound care.
Keywords: Ethnopharmacology, drug development, herbal medicine, wound healing, and phytochemicals